Inkulturasi Nilai Moderasi Beragama di Lembaga Pendidikan Dasar Desa Multi Agama Lamongan - Trista Febbrianti; Ayu Afita Sari; Bayu Sukmo Raharjo; Lusia Mumtahana (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2022)
The purpose of this study is to describe the strategies used by educators at Public Elementary School 1 Balun Turi Lamongan as a multi-religious school in an effort to instill the values ​​of religious moderation, as well as the implementation of moderation values ​​applied by educators at Public Elementary School 1 Balun Turi Lamongan towards learners. Public Elementary School 1 Balun Turi Lamongan is a multicultural elementary school that has a variety of cultures, races, ethnicities and religions, therefore it is not uncommon for these differences to lead to conflict. From an early age, extreme and radical thoughts must be eliminated as soon as possible. This study uses a descriptive qualitative method with a phenomenological approach. From the results of the research that we got at Public Elementary School 1 Balun Turi Lamongan, a strategy in inculcating the value of religious moderation is applied in teaching and learning activities and outside teaching and learning activities. There are many ways that educators do in inserting knowledge about mutual respect and tolerance in every learning and habituation. This shows that the values ​​of moderation have been embedded in each student so that it can be concluded that the inculturation of religious moderation values ​​at Public Elementary School 1 Balun Turi Lamongan is quite effective so that it can be applied to multi-religious basic education institutions elsewhere.